Perancangan Sistem Monitoring Konduktivitas dan Padatan Terlarut PDAM Banyumas Berbasis IoT - Indah Permatasari; Nia Annisa Ferani Tanjung; Nur Afifah Zen (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
PDAM is a company engaged in the distribution of clean water for the community. Some Indonesian people have become PDAM water customers to meet their water needs for their daily activities. Water quality is an important issue because it is closely related to health. In this paper, the design of the water quality monitoring system in PDAM Banyumas based on IoT is carried out by reviewing the parameters of electrical conductivity (EC) and dissolved solids (TDS). The result of measurement data can be accessed via the Android App on smartphone. The application is designed using HTTP and MQTT protocols. HTTP protocol is used on the user interface to retrieve the last measurement data. Meanwhile, the MQTT protocol is used to update measurement data so that the data transmission process is faster. The system will send notification via telegram if the water quality is below quality standard. The measurement accuracy test is done by comparing the monitoring device with the certified measuring instrument on samples of bottled drinking water and PDAM water. The results show that the performance of the designed monitoring device was 97.31% and the quality of the PDAM Banyumas water is very stable and safe for consumption.